Cross-cultural adaptation and validity of the Italian version of the Central Sensitization Inventory. (October 2018) - Chiarotto, Alessandro; Viti, Carlotta; Sulli, Alberto; Cutolo, Maurizio; Testa, Marco; Piscitelli, Daniele
Abstract: Background: Central sensitization (CS) is an important feature in patients with chronic pain. The Central Sensitization Inventory (CSI) was developed with the goal of detecting the patients' symptoms related to CS. Objectives: This study aimed at cross-culturally adapting the CSI into Italian, and at assessing its structural and construct validity in patients with different chronic pain disorders. Design: Clinimetric study. Methods: The Italian version of the CSI (CSI-I) was generated following forward and backward translations, expert committee review, and pilot-testing. Patients with pain for ≥3 months were eligible if diagnosed with: low back pain (LBP), temporomandibular disorder (TMD), hand osteoarthritis (HOA), fibromyalgia (FM), or rheumatoid arthritis (RA). Structural validity was assessed with exploratory factor analysis and parallel analysis based on minimum rank factor analysis; construct validity was evaluated by testing ten hypotheses on: 1) expected differences between relevant subgroups, 2) expected correlations with other instruments measuring pain intensity, physical functioning, psychological functioning, headache symptoms, and pain self-efficacy. Results: 220 patients were included: 35% with LBP, 17% with TMD, 19% with HOA, 9% with FM, and 20% with RA. Factor analyses revealed that the CSI-I is a unidimensional instrument. Construct validity was satisfactory since 80% of the hypotheses were met. Conclusions: The CSI-I was successfully developed and exhibited satisfactory validity in patients with chronic pain. Its reliability, responsiveness and content validity should be investigated in future studies. Until robust evidence indicates a strong relationship between CS and the CSI-I, caution should be adopted in claiming that the CSI-I measures CS. Highlights: The CSI was successfully cross-culturally adapted into Italian (CSI-I). The CSI-I is a unidimensional instrument in patients with chronic pain. The CSI-I construct validity was satisfactory according to hypotheses testing. Future studies should assess the CSI-I reliability and responsiveness. The CSI content validity remains unclear and should be evaluated.